African swine fever virus replication methodology to facilitate production of vaccine candidate - CGIAR Research Program on Livestock (2018)
This innovation makes it possible to synthetically modify viruses on the DNA level followed by initiating replication for production of variants which facilitate production of vaccine candidate.